2008
DOI: 10.1007/s00248-008-9434-3
|View full text |Cite
|
Sign up to set email alerts
|

Plankton Community Succession in Artificial Systems Subjected to Cyanobacterial Blooms Removal using Chitosan-Modified Soils

Abstract: Using artificial systems to simulate natural lake environments with cyanobacterial blooms, we investigated plankton community succession by polymerase chain reaction-denaturing gradient gel electrophoresis (PCR-DGGE) fingerprinting and morphological method. With this approach, we explored potential ecological effects of a newly developed cyanobacterial blooms removal method using chitosan-modified soils. Results of PCR-DGGE and morphological identification showed that plankton communities in the four test syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…The algal blooms remove was conducted by chitosan-modified soils in experimental area in August, 2008. The composition of chitosan-modified soils and the methods of algal blooms removal were described by Pan et al (2006a) and Yan et al (2009). Planktonic organisms for qualitative and quantitative analysis were collected and pretreated according to Yan et al (2007).…”
Section: Collection and Processing Of Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The algal blooms remove was conducted by chitosan-modified soils in experimental area in August, 2008. The composition of chitosan-modified soils and the methods of algal blooms removal were described by Pan et al (2006a) and Yan et al (2009). Planktonic organisms for qualitative and quantitative analysis were collected and pretreated according to Yan et al (2007).…”
Section: Collection and Processing Of Samplesmentioning
confidence: 99%
“…However, as major primary producers, impact of algal blooms removal on high trophic levels is important during treatment. Even the process of algal blooms removal by chitosan-modified soils unaffected the growth of Local mussels Cristaria plicata (Leach) and submerged macrophytes Myriophyllum spicatum (Zou et al, 2006), as well as Yan et al (2009) proved neither chemical conditions nor plankton succession are significantly affected by the algal removal process in artificial systems, the effect on natural freshwater ecology is still unclearly after this process. A comparison of zooplankton community between pre and post algal blooms removal (July 21, 2008 andAugust 22, 2008, respectively) showed that there was significant diversity (paired samples test, p = 0.035, the result unpublished).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Yan et al [15][16][17][18]20,21] applied different fingerprinting approaches to investigate relationships among the genetic diversity of plankton communities, species composition and environmental factors in aquatic environments of lakes, rivers, and reservoirs. Results indicated that the DNA fingerprints of target communities were generally correlated with species composition of plankton and their environments [15][16][17][18]20,21]. The concentration of TP was found to be the major factor in determining plankton communities derived from eutrophic environments [19].…”
Section: Community Fingerprinting Analysismentioning
confidence: 99%
“…To date, large numbers of metagenome-based studies on bacterioplankton and more recently on eukaryotic picoplankton have been undertaken (e.g., [11][12][13][14]). Targeting the plankton community as a system, Yan et al [15][16][17][18] and Yu et al [19] currently applied fingerprinting techniques to investigate the relationships between DNA polymorphisms and species composition of plankton communities in different habitats and environments (i.e., lakes, rivers, reservoirs, ponds, enclosures, and artificial systems). As community composition is largely dictated by environmental factors, it has been a natural extension of this relationship to use plankton community fingerprints as an indication of environmental conditions [17][18][19][20][21].…”
mentioning
confidence: 99%
See 1 more Smart Citation